People, Power and Profits: Progressive Capitalism for an Age of Discontent - Thwaites, James (Relations industrielles / Industrial Relations, 2022)
This article reviews the book, "People, Power and Profits: Progressive Capitalism for an Age of Discontent," by Joseph Stiglitz.